ВПЛИВ МАРКСИЗМА ТА НЕОМАРКСИЗМА НА ДОСЛІДЖЕННЯ НАЦІОНАЛІЗМУ - БАГІРОВА, ЛАЛА (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
У статті розглядаються концепції основних теоретиків націоналізму, котрі спираються або знаходяться під впливом ідей марксизму та неомарксизму. Аналізується, в чому проявляється вплив марксизму на дослідження націоналізму, який потенціал можуть мати ідеї марксизму для дослідження націоналізму, та яку критику вони можуть викликати. Лала Багирова ВЛИЯНИЕ МАРКСИЗМА И НЕОМАРКСИЗМА НА ИССЛЕДОВАНИЯ НАЦИОНАЛИЗМА В статье рассматриваются концепции основных теоретиков национализма, которые отталкиваются от идей марксизма и неомарксизма, либо находятся под их влиянием. Анализируется, в чем проявляется влияние марксизма на исследования национализма, какой потенциал могут иметь идеи марксизма для исследований национализма, и какую критику они могут вызывать. Ключевые слова: национализм, неомарксизм, марксизм, капитализм. Lala Bagirova THE INFLUENCE OF MARXISM AND NEOMARXISM ON NATIONALISM STUDIES The theories of the investigators of nationalism, influenced by marxist and neomarxist ideas are regarded in the article. The influence of marxism on nationalism studies is analyzed. The potential of Marxist ideas in nationalism studies is regarded. The possible critic is analyzed. The Marxist critics suppose that economic factors play a great role in the process of national creation. The character of work and capitalism make the culture homogeneous which can be called the beginning of the nation. The unified educational system and homogeneous culture are the result of the changes in the character of work. The national movement and the class struggle have much on common. In the contemporary world nationalism can be called nationalism of classes. European nationalism against emigrants should be regarded as a phenomenon based on class factors and inspired by the competition for jobs, conditions of living and goods. Nation can be possible only in the society of a certain type. This should by an industrial society with well-developed institutions of school and family. These institutions play a role of transmission of the national ideology. The paradox is that in the modern world of transnational economics and worldwide work migration nation is still the only possible form of political organization. Transnational projects like European Union may play the role of economic regulation but are helpless when it comes to identity, language or law. Nation does not lose its positions even in the world of global culture. The members of nationalistic social groups might listen to hard rock, wear jeans and eat Chinese foods. This proves that the nation successfully stands against the challenges of global culture and global economics. The potential of Marxist approaches to analyses of nationalism is great. They can easily be combined with constructivist theories and give great scientific results. The possible critics can be concentrated on the contemporary situation, because nation still plays a great role in the transnational and transeconomic world. Keywords: nationalism, neomarxism, marxism, capitalism